The Influence of Digital Skills on Elementary School Teachers’s Performance in Semarang City with Digital School Governance as a Moderating Variable - Wijayanti, Dian Marta; Pramono, Suwito Eko; Handoyo, Eko; Sugi, Sugi (Universitas Negeri Semarang, 2025)
This study was conducted in Semarang City with a mixed method approach and explanatory sequential design to gain an in-depth understanding of the influence of digital skills on teacher performance with digital governance as a moderating variable. The novelty of this study lies in the simultaneous testing of the influence of digital skills on teacher performance, while exploring the moderating role of school digital governance in the relationship between these variables which has not been comprehensively studied in the context of primary and secondary education. The results of the quantitative analysis show that digital skills have a positive and significant effect on teacher performance (t = 3.555; β = 0.198; p = 0.003), as well as school digital governance which has the strongest influence (t = 14.504; β = 0.691; p = 0.000). Meanwhile, the results of the moderation test show that the moderating variable does not have a significant effect (t = 1.171 < t-table 1.967), so it does not strengthen or weaken the relationship between variables. Digital skills have an effect on teacher performance. Meanwhile, the tested moderating variables did not have a significant effect, indicating that these factors neither strengthen nor weaken the relationship between the main variables. This study provides theoretical and practical contributions in the development of a digital-based teacher performance model. The main recommendations are the need for policies to continuously improve teachers' digital capacity, strengthen the digital leadership of school principals, and optimize the school's digital governance system as a strategy to improve teacher performance that is relevant to the demands of educational transformation in the digital era.